Analisis Postur Kerja Menggunakan Metode Rapid Entire Body Assessment (REBA) Dengan Inovasi Meja Penjemuran Kerupuk di UMKM Kerupuk Subur - Rangga Sidiq Permana; Triyana Triyana; Fahmi Husaeni; Irfan Bukhori; Khotibul Umam; Andung Jati Nugroho (Fakultas Teknik Universitas Cenderawasih, 2024)
In the cracker production process at UMKM Kerupuk Subur, the process of drying crackers involves human labor so there is a risk of injury because when drying crackers, workers have to bend and squat. This study aims to determine the occupational dangers of workers during the drying process of crackers in UMKM Kerupuk Subur and provide recommendations for improvement. The method used to analyze body posture is Rapid Entire Body Assessment (REBA) then for improvement recommendations using an anthropometric approach with percentile calculations to determine dimensions as parameters for designing the work aids needed in the form of an ergonomic drying table. The results of REBA's analysis show a score of 9 with a high or high level, meaning there is a high risk of injury so immediate improvement is needed. The results of the design of an ergonomic drying table were then simulated through Inventor software which described the position of the worker's posture when carrying out cracker drying activities with a perpendicular working position. The results of the assessment of the working posture of the worker after the improvement showed a decrease in the risk level from medium to low and negligible.